The social and ecological integration of captive-raised adolescent male African elephants (Loxodonta africana) into a wild population. - Kate Evans; Randall Moore; Stephen Harris (PLoS ONE, 2013)
BACKGROUND: A rapid rise in the number of captive African elephants (Loxodonta africana) used in the tourism industry in southern Africa and orphaned elephants in human care has led to concerns about their long-term management, particularly males. One solution is to release them into the wild at adolescence, when young males naturally leave their herd. However, this raises significant welfare concerns: little is known about how well released elephants integrate into wild populations and whether they pose a greater threat to humans than wild elephants. We document the release of three captive-raised adolescent male African elephants in the Okavango Delta, Botswana. METHODOLOGY/PRINCIPAL FINDINGS: Despite having been part of a herd of working elephants for at least eight years, the three males progressively integrated into the complex fission-fusion society of wild bull elephants. In the three years following release, they showed no tendency to be closer to human habitation, and there were no significant differences between wild and captive-raised adolescent males in the total number of social interactions, size of ranges and habitat use. However, the captive-raised elephants sparred less and vocalised more, and spent more time alone and in smaller social groups. Thereafter the released elephants continued to expand their ranges and interact with both mixed-sex herds and males. One male was shot by farmers 94 months after release, along with ten wild elephants, on a ranch outside the protected area. CONCLUSIONS/SIGNIFICANCE: We show that captive-raised adolescent male elephants can integrate into a wild population. Long-term studies are required to determine the longevity, breeding success, and eventual fate of released male elephants, but we identified no significant short-term welfare problems for the released elephants or recipient population. Release of captive-raised mammals with complex social systems is a husbandry option that should be explored further.